Conditional Income Disparity between Farm and Non‐farm Households in the European Union: A Longitudinal Analysis. (19th January 2021) - Marino, Maria; Rocchi, Benedetto; Severini, Simone
Abstract: Government interventions in the agricultural sector have been historically justified by the existence of an income disparity between farmers and non‐farmers. However, recent studies have found that such disparity is disappearing over time, particularly in the United States. This work offers the first longitudinal systematic assessment on the average income disparity between farm and non‐farm units in the European Union, differentiating between old and new Member States. Using the EU‐SILC dataset, both broad (having some farm income) and narrow (living mainly on agriculture) farm households are compared with a general sample of non‐farm households and a more restricted sample of self‐employed non‐farm households. To control for household observable characteristics and time‐constant unobserved factors, we use a fixed effects regression. Results suggest that the farm/non‐farm income disparity has disappeared in the European Union unless we compare narrow farm households with all non‐farm households: in this case, the former are more likely to be better off than the latter. A limited income disparity is found only in the case of new Member States for broad farm households only. Results are used to draw policy implications regarding the role of CAP in supporting farm income.